La Vinculacion De Los Conocimientos Academicos Y Los Saberes Ancestrales En La Educacion Básica Intercultural En Presidio De Los Reyes, Nayarit México - Cueto, María del Carmen Hernández; Hernández, María del Refugio Navarro; Pérez, Master Lía Márquez (European Scientific Journal, ESJ, 2018)
This paper focuses on analyzing the teaching-learning process that takes place in second level basic education in the community of Presidio de los Reyes in Nayarit, Mexico. The study aims at knowing if this links the ancestral knowledge of the Naayeri community (Cora) with the official academic curriculum of the Ministry of Public Education (MPE). The study sample were the teachers and the management staff of Pentecatl Elementary located in a community in Cora baja, in the municipality of Ruiz in Nayarit, Mexico. The methodology of this study was transversal for one year and then qualitative. The instruments used in this study was a semi-structured interview about the knowledge of the basic education profile, as well as the analysis of the teaching sequences of the teachers. The results of the research show how teachers promote traditional knowledge, culture, and the learning of the Cora language as a national language and not as a mother tongue. They design materials and perform activities that relates and links traditional knowledge with academics. They also establish approaches with the traditional authorities, and bridges are being constructed that intertwine the ancestral knowledge with the academic contents proposed by the MPE.